Studi Literatur: Internalisasi Nilai-Nilai Akhlak Mahmudah pada Era Digital - Mellani Putri Rahayu Buwono; Mohamad Joko Susilo (Jurnal Eduslamic, 2025)
This study stems from the phenomenon of the gap between the idealism of Islamic boarding school (pesantren) education, which is rich in moral values, and the reality of students' behavior influenced by digital culture. The research aims to describe how the process of internalizing akhlak mahmudah (noble character values) takes place in pesantren in facing the challenges of the digital era.This study uses a literature review approach by examining relevant scholarly sources on the internalization of akhlak mahmudah values in pesantren during the digital era. The findings show that internalization occurs through three stages: value transformation, transaction, and transinternalization, which are strengthened through the strategies of exemplary behavior, habituation, supervision, and integration of values into pesantren culture.Digital challenges such as uncontrolled access to information, lifestyles driven by social media trends, and weak character-based digital literacy are major concerns in education, particularly within the pesantren context. This study offers a fresh perspective by highlighting the importance of adaptive and contextual strategies in nurturing students’ character so that it remains relevant amid the intense flow of digital influence.